10 - Capitalist Globalisation and the Role of the International Community in Resource Conflicts in Africa: https://doi.org/10.4314/ad.v34i3-4.63535 - Amuwo, Adekunle (Africa Development, 2009)
The principal thesis of this paper is that under contemporary capitalist globalisation, the so-called international community constitutes more of the problem than the solution in the continent’s resource and allied conflicts. We argue that the geo-strategic and geo-political interests of major western and other powers and the transnational capitalist class (TCC), which tend to defend and enhance these interests, have over the past several decades either been the root cause of resource con- flicts on the African continent or have fuelled, exacerbated and pro- longed them. The almost devotional attitude of the continent’s ruling elites to the values and institutions of capitalist globalisation – and its resultant unequal distribution of the gains and pains of market reforms – have equally contributed to resource conflicts. While there is a complex interplay between internal and external factors and actors, on-balance external causation has, by far, dwarfed internal explanations of con- flicts. African societies and peoples have thus suffered an unmitigated internationalisation, exploitation and pillage of their rich tropical hard- wood, gems, mineral and oil resources. The paper proposes a strategic coalition of victims of capitalist globalisation and capitalist militarisation in Africa and elsewhere (nations, societies, communities and peoples) to systematically confront and oppose the most invidious rocess that has turned Africa’s resource blessing into resource burden.